Učni stili in preference za opravljanje bodočega poklicnega dela študentov in študentk dodiplomskega študija kineziologije - Plevnik, Matej; Babnik, Katarina (Revija za elementarno izobraževanje, 2020)
Learning styles and preferences for future professional work among undergraduate kinesiology students. We presented the results of a study in which 107 students of kinesiology participated. Using the Felder-Silverman and Questionnaire, we noted their learning styles and their preferences for work after graduation. We found that objective conclusions about preferential learning styles cannot be reached, because of the identified limitations of the four scales of the questionnaire. Therefore, we presented the proportion of choices between alternative responses that characterize each learning style and the proportion of preferred approaches to teaching within the study process and forms of teaching materials.
Keywords: intellectual styles; work preferences; higher education; kinesiology